Culinary MSMEs Accounting System Design: “Pempek Lin Friends Palembang” - Erlyna Juany; Meiliana Suparman (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
The majority of MSMEs in Indonesia are lack of adequate accounting records. Therefore, it is difficult to estimate the volume of their financial transactions and develop their business. The objective of this community service project is to provide a tailored accounting system for " Lin Friends Pempek Palembang" complied with SAK-EMKM. This project used primary data obtained from interviews, observations, simulations, and documentation. The data obtained were grouped and analyzed to develop a tailored accounting system. The design of the system began with compiling charts of accounts and menus to record data of customers, suppliers, and raw materials. As part of the design, this project used a special journal system to compose recording menu, including general journals, and purchase journal, production journal, sales journal, cash payment and received journal. The final step in the design process was preparing menus for obtaining financial statements and other reports. As the result of this project implementation, partners now understand the importance of financial information from their businesses and are able to produce and use financial reports. They can increase their net profit, estimate their monthly transactions, and forecast raw material requirements, which result in better financial management.